The use of gloves by the nursing team in a hospital environment - Caroline do Rio; Camila Eugenia Roseira; Lívia Cristina Scalon da Costa Perinoti; Rosely Moralez de Figueiredo (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to verify the compliance rate of the use of gloves by the nursing team in a hospital environment. Methods: a descriptive study, carried out in a hospital in the state of Sao Paulo, Brazil, between August and October 2019, through the observation of the nursing team in carrying out a total of 396 procedures. All ethical aspects were considered. Results: 32 different types of procedures were observed. The compliance rate with the use of gloves occurred only in one observation (0.25%). Excluding hand hygiene, it was 60.1% (238). In other 158 (39.9%) opportunities, incorrect use varied between reuse (18.43%), unnecessary use (8.33%) and non-use when necessary (13.13%). Hands were cleaned before using gloves in 1.76% of the observations and in 4.54% immediately after their removal. Conclusions: non-conformities were identified in the use of gloves when observing the performance of procedures by the nursing team.